Effect of Indoleacetic Acid and Zinc Sulphate Application on Growth and Some Physiological Parameters of Cowpea (Vigna sinensis Savi) Plants - Tahir, Ikbal Muhammed Gharib; Khudur, Sargul Ahmad; Anwar, Arol Mohsen (Kurdistan Journal of Applied Research, 2019)
This study was conducted in Koya city, Iraq on cowpea (Vigna sinensis Savi) plants California black eye variety by factorial experiment including the effects of foliar spraying of Zinc Sulphate ZnSO4.7H2O (ZS) or the plant growth regulator Indoleacetic Acid C10H9NO2 (IAA). Analysis of data revealed that ZS and IAA application affects significantly on the studied traits. 100 ppm of IAA increased significantly the leaves content of each of chlorophylls a, b, and total, although it decreased the content of total carotenoids. The results showed that the leaf area significantly increased by increasing the amount of ZS to 2.0 g/L compare with other treatments except 1.0 g/L ZS application. Foliar application of IAA increased significantly the dry matter percent of shoots and roots as well as the number of nodules per plant. It has been found that leaves content of zinc is related to the concentration of ZS applied significantly compared to the control and IAA treatments, however, the application of IAA caused to decrease K and Zn contents in leaf of the plants compared to other treatments. Finally, based on the results the best ratio of IAA for increased stomata number on the abaxial and adaxial leaves surfaces was 75 ppm.